Oral L-Arginine lower neovascularization and the number of fibroblasts but failed to increase nitric oxide and epithelialization in the healing process of male white diabetic wistar rats (Rattus norvegicus) - Fenni Liem; Wimpie Pangkahila; I Wayan Weta (Fakultas Kedokteran Universitas Udayana, 2019)
Introduction: Oral L-Arginine is a conditional essential amino acid that plays a role in wound healing in DM. The role of arginine in diabetic wounds is by enhancing blood circulation in the injured area and increasing oxygen supply to the wound tissue. The purpose of this study to prove the administration of oral L-Arginine toward vascularization status in wound healing of male white rats wistar diabetes mellitus. Methods: A randomized posttest only control group study using with 36 diabetic induced wistar rats (Rattus Norvegicus) aged 2-3 months and weighing 180-200gram which then divided randomly into two groups. Nitric oxide level was measured on the third day and each group was then further divided into two groups for examination of neovascularization, fibroblasts and epithelialization on the seventh day and on the tenth day. Results: Administration oral L-Arginine failed to induce any significant change in Nitric Oxide level and wound gap closure. On the other hand, the results showed that the mean neovascularization was significantly different between the two groups on the 10th day (Control group vs intervention group: 4.22±1922 vs1.89±1364; p=0.009). In addition, the mean number of fibroblast at the 10th day was also significantly different (Control group vs intervention group: 74.11±28.57 vs 38.11±20.90; p=0.008). Conclusion: In conclusion, oral L-Arginine did not significantly affect nitric oxide and epithelialization while decreased neovascularization and the number of fibroblasts on day tenth in the healing process of male white rats diabetes mellitus